Introduction to Atomic Spectrometry - Reid, Helen; Summerfield, Stephen (The University of Hull)
An introduction to atomic spectrometric analysis, describing the basic principles of each technique, their application areas and modes of operation, including practical comparison of the techniques. It is illustrated with simple diagrams and photographs of equipment.